Surviving and thriving in turbulent times - Cendon Eva; Halttunen Timo; Orr Kevin (eucen, 2025)
The eucen ULLL Open Fora is a series of short activities that takes place over the course of one month, highlighting four hot topics in each of the four weeks. eucen started this during the first year of the Covid-19 pandemic, in November 2020, when all in-person activities had been cancelled. The ULLL Open Fora provide a stage for short presentations and focused indepth discussions, each week starting with a master class - an introduction to the topic by a well-known expert from academia, policy, or business sharing his or her insights. After short presentations on each subsequent day, the week concludes with a panel discussion on the week’s topic with key stakeholders and presenters. A collection of papers based on the eucen ULLL Open Fora 2020 has already been published in the former eucen eJournal of University Lifelong Learning (eucen, 2020).